(untitled) (Gilgameš, 2019)
This paper examines the sixteenth century tradition of the inscription CIL V, 5267, found in Como in 1511 and currently exhibited at Civico Museo Archeologico P. Giovio. This inscription preserves the cursus honorumof Calpurnio Fabato who, as a political figure of considerable importance, has been mentioned by various literary sources. The text of the inscription is difficult to read, due to the bad state of the conservation of the basis; since the discovery scholars proposed several transcriptions. The aim of this paper is to highlight and analyse some of the variances that can be found in the transcriptions.